Relation of Neck Circumference to Central Obesity and Overweight in Patients with Type 2 Diabetes Mellitus Presenting to a Tertiary Center - Sharma, Ishwor; Gupta, Sanjay K; Niraula, Kiran (Journal of Institute of Medicine Nepal, 2020)
Introduction Overweight and obesity with their surrogate anthropometric markers like body mass index (BMI), waist circumference (WC) and waist hip ratio (WHR) have been shown to be strongly associated with Type 2 diabetes mellitus. Neck circumference (NC) though less used can be an equally effective alternative to diagnose overweight and obesity in patients with Type 2 diabetes mellitus in a resource limited setting. Methods Patients who had Type 2 Diabetes Mellitus for 5 years or more and above 35 years underwent simple random sampling. Weight, height, WC and NC were measured. BMI was calculated and patients were graded into overweight and obesity based on the Asian cutoffs for BMI and abdominal obesity. Results Among 100 patients enrolled in this study, 45% were men and the mean age was 53.05. Mean neck circumference was 36.55 ± 1.28 cm and 35.27 ± 1.78 cm for male and female respectively. NC was positively correlated with WC and BMI in both men and women (p ˂ 0.001). In the ROC curves, NC presented the largest area under the curve (AUC) for overweight in males (p ˂ 0.001), while NC presented a large AUC for central obesity in both genders. Furthermore, the cut off value of neck circumference for overweight was 35.6 cm in males vs 35.2 cm in females and for central obesity was 36.75 cm in males vs 34.75 cm in females. Conclusion Neck circumference was positively associated with overweight and central obesity in patients with type 2 diabetes mellitus.